Penambahan Ekstrak Jahe dalam Pakan untuk Meningkatkan Produksi Kelompok Pembudidaya Ikan di Desa Winorangian Kabupaten Minahasa Tenggara - Henky - Manoppo; Steelma Vivera Rantung (Gorontalo Fisheries Journal, 2019)
The purpose of this experiment was to improve the growth and survival if fish.  This wwas done to help solving the problems of poor growth and frequent diasese outbreak faced by fish farmers group (pokdakan).  The fish used was Nile tilapia which was stocked at  a 1000 m2 pond at a density of 10 fish/m2.  After two weeks of aclimatization process, the fish was fed pellet supplemented with 7.5 g ginger powder per kg of feed.  Feeding time was 30 days at 5% of body weigth per day with a feeding frequency of three time a day.  Sampling of fish weight was carried out at day 30th. The result showed that after 30 days of feeding, the weight of fish (initial weight 5±0.6 g/fish) achived 17.5 g in average. The average daily growth was 4.2%. There was no mortality due to disease attack during the feeding trial. So the use of ginger extract can improve growth and survival of cultivated fish.